Phylogenetics of Paepalanthus (Eriocaulaceae), a diverse Neotropical monocot lineage. (3rd September 2020) - Andrino, Caroline O; Sano, Paulo T; Inglis, Peter W; Hensold, Nancy; Costa, Fabiane N; Simon, Marcelo F
Abstract: Paepalanthus is a diverse monocot genus with remarkable diversity distributed in the Neotropical highlands of South America. The genus comprises 410 species arranged in subgenera, sections, subsections and series. Added to this complex classification, Paepalanthus shows considerable morphological heterogeneity and includes three other genera in it, Actinocephalus (Körn.) Sano, Lachnocaulon Kunth and Tonina Aubl. A broadly sampled phylogenetic inference for the genus is still missing, precluding a better understanding of its delimitation and further studies in the group. Here we present the most comprehensive phylogenetic study for Paepalanthus to date, as well as morphological survey of characters that delimit the main lineages found. We assembled a morphologically and geographically representative sampling of Paepalanthus and associated genera comprising 356 accessions in a combined dataset of plastid ( trnL-F, psbA-trnH ) and nuclear (ITS, ETS) regions. Bayesian inference and maximum likelihood methods were used for phylogenetic reconstruction. We found that Paepalanthus and 16 of its 28 infrageneric categories are not monophyletic, as well as the closely related genus Actinocephalus . Thirty-six well-supported clades are recognized. Morphological characters show high levels of homoplasy, and concepts traditionally used in the classification of Paepalanthus were found to be inconsistent. We confirmed that Paepalanthus as currently circumscribed is not monophyletic and revealed several new relationships in Eriocaulaceae. To make Paepalanthus monophyletic, the genus must be re-circumscribed. These results also provide a foundation for future investigations of the diversification and evolution of flora of the Neotropical highlands of South America.